Correspondence between Florence O'Donoghue and various individuals regarding his research for his book 'No Other Law: The Story of Liam Lynch and the Irish Republican Army, 1916-1923' - O'Donoghue, Florence, 1895-1967; Leddy, Con, 1891-; Meaney, Cornelius; Coss, James (1950)
Correspondents are Patrick Coughlin, Michael J. Hyland, Con Leddy, James Coss, Con Meaney, Ned Murphy, Michael O’Connell, Ned O’Brien and Dónal Óg O’Callaghan. Topics include the officers of the Cork No. 2 Brigade of the I.R.A. Includes original red sleeve which contains the correspondence.
Keywords: O'Donoghue, Florence, -- 1895-1967 -- Correspondence; Lynch, Liam, -- 1893-1923; Irish Republican Army; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-